OsmoseLua – An Integrated Approach to Energy Systems Integration with LCIA and GIS - Yoo, Min-Jung; Lessard, Lindsay; Kermani, Maziar; Maréchal, François (Computer Aided Chemical Engineering, 2015)
In this paper, we present our recent work on the implementation of an Energy Systems Integration platform allowing the modeling of Energy Systems integrating LCI (Life Cycle Inventory), LCIA (Life Cycle Impact Assessment) and GIS (Geographical Information Systems) data as modeling parameters and variables included in an industrial process model. Based on our previous experience in methodologies and models of Energy Systems Integrations, we developed a new generation of the platform using the script language Lua. The main motivation for choosing Lua was to radically improve the performance of the system, which was the main drawback of the existing Matlab-based system, while proposing a more convenient way of describing the modeling elements and their combination. The second objective of our work was to integrate LCI and LCIA aspects as a generic part of the Energy Systems modeling methodology. We are currently working on the process data mapping algorithm in order to match the appropriate Unit process and Elementary flows identifiers used in the ecoinvent v3 database. Thirdly, by having the possibility of importing GIS databases (in csv format), some coordination data, such as longitude and latitude, can be directly included as Energy System elements’ location parameters. This possibility improves the efficiency in modeling the energy integration of urban systems.